Morphological differentiation of severe aplastic anaemia from hypocellular refractory cytopenia of childhood: reproducibility of histopathological diagnostic criteria - Baumann, Irith; Fuehrer, Monika; Behrendt, Sonja; Campr, Vit; Csomor, Judit; Furlan, Ingrid; De Haas, Valerie; Kerndrup, Gitte; Leguit, Roos J.; De Paepe, Pascale; Noellke, Peter; Niemeyer, Charlotte; et al. (Histopathology, 2012)
To evaluate the reproducibility and reliability of the histomorphological criteria differentiating severe aplastic anaemia (SAA) and hypoplastic refractory cytopenia of childhood (RCC), the most frequently acquired hypocellular bone marrow conditions of childhood.We performed a double-blind interobserver study of 100 different cases of SAA and RCC among seven haematopathologists of the European Working Group of MDS in Childhood (EWOG-MDS) and the German SAA study. Cases with foci of typical myelodysplastic syndrome (MDS) morphology, such as patchy erythropoiesis with defective maturation, in an otherwise highly hypocellular or adipocytic bone marrow were classified as having RCC. Bone marrow samples without a patchy distribution, few scattered myeloid cells or haematopoietic aplasia were diagnosed as SAA. In only four of 100 cases did the reference pathologists not reach agreement regarding classification as SAA or RCC. The kappa index was 0.79.Our results show that the vast majority of SAA and RCC cases can be reliably differentiated by morphological means alone. A clear differentiation between SAA and RCC at presentation is mandatory for optimizing therapy strategies, and might be responsible for the fact that, in the German childhood SAA study, the probability of developing clonal disease after immunosuppressive therapy has dropped to 3%.
EVALuna2:6412